Hämophilie-A-Patienten und Konduktorinnen für Hämophilie A - Delbrück, C.; Haferland, I.; Scholz, K.; Asmelash, G.; Makki, V.; Müller, S.; Krekeler, S.; Alesci, S.; Miesbach, W. (Hämostaseologie, 2011)
The retrospective cohort study surveys the influence of age, co-morbidity and laboratory values on FVIII-activity (FVIII : C) in patients with haemophilia A with (mild n = 48, moderate n = 10, severe n = 7 and carriers n = 23). Median observation was 19 years for patients with haemophilia A and 9,5 years for carriers.Results FVIII : C levels collected from patients with mild haemophilia A displayed a significant median increase of 6.5% with proceeding age (p = 0.0013). Patients with moderate haemophilia A (and carriers of haemophilia A) showed a non significant median increase of 1.05% (carriers 8%). Eight patients showed FVIII : C levels at last blood withdrawal that indicated a change of severity from moderate to mild haemophilia A. A significant correlation was found between FVIII : C and VWF : RCo (p= 0.0203) and AFP (p < 0.0005). The correlation between FVIII : C and triglycerides and LDH was significant negative (p < 0.0005). No significant correlation could be found for FVIII : C and co-morbidity, fibrinogen, cholesterol and VWF : Ag.
Keywords: Haemophilia A; age; FVIII : C; variability